Branching in Pea (Action of Genes Rms3 and Rms4). - Beveridge, C. A. (1996)
The nonallelic ramosus mutations rms3-2 and rms4 of pea (Pisum sativum L.) cause extensive release of vegetative axillary buds and lateral growth in comparison with wild-type (cv Torsdag) plants, in which axillary buds are not normally released under the conditions utilized. Grafting studies showed that the expression of the rms4 mutation in the shoot is independent of the genotype of the root-stock. In contrast, the length of the branches at certain nodes of rms3-2 plants was reduced by grafting to wild-type stocks, indicating that the wild-type Rms3 gene may control the level of a mobile substance produced in the root. This substance also appears to be produced in the shoot because Rms3 shoots did not branch when grafted to mutant rms3-2 rootstocks. However, the end product of the Rms3 gene appears to differ from that of the Rms2 gene (C.A. Beveridge, J.J. Ross, and I.C. Murfet [1994] Plant Physiol 104: 953-959) because reciprocal grafts between rms3-2 and rms2 seedlings produced mature shoots with apical dominance similar to that of rms3-2 and rms2 shoots grafted to wild-type stocks. Indole-3-acetic acid levels were not reduced in apical or nodal portions of rms4 plants and were actually elevated (up to 2-fold) in rms3-2 plants. It is suggested that further studies with these branching mutants may enable significant progress in understanding the normal control of apical dominance and the related communication between the root and shoot.